Teacher's Strategy in Implementing the Independent Learning Curriculum in the Leading Regions, Remote, and Left Behind (3T) - Baene, Marelius; Piliang, Hasrul; Fatmariza, Fatmariza; Darmansyah, Darmansyah (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aims to determine the strategies teachers use in carrying out independent learning curriculum learning in frontier, remote, and disadvantaged schools and to explain the limitations in frontier, remote, and disadvantaged areas. The method used in this research is qualitative with a case study approach. This research was conducted at SMP Negeri 2 Amandraya in South Nias district, North Sumatra province. Data collection techniques were carried out through interviews, observation, and documentation. Informants in this study consisted of 10 teachers, principals, and 20 students. Data analysis was done using data reduction, presentation, and conclusion. The results of the study show that the teacher's strategy in implementing the independent learning curriculum in frontier, remote, and disadvantaged areas is that the teacher optimizes the use of available learning facilities, the teacher utilizes learning tools and materials that are made naturally, and the teacher uses internal creativity in supporting learning by independent learning curriculum. Teacher competence in implementing the independent learning curriculum has limitations, namely the need for teacher training and professionalism. In addition, the results of implementing the independent learning curriculum have yet to experience changes in student learning outcomes fully. Therefore, the researchers suggest that local governments focus on developing human resources and learning facilities in frontier, remote, and underdeveloped regional schools to create young people who can compete nationally and internationally.